Leadless Pacemaker Implantation in Prosthetic Valve Endocarditis Patient: Lesson with the Micra Transcatheter Pacemaker - Maurizio, Santomauro; Andrea, Santomauro; Antonio, Rapacciuolo; Carla, Riganti; Francesco, Maffettone; Francesco, Fiore; Martina, Iengo; Rosaria, Chiappetti; Francesco, Cacciatore (Cardiology and Cardiovascular Medicine, 2021)
Leadless Pacemakers (L-PM) are an effective alternative for patients requiring only ventricular pacing, with a low major complication rates and long-term complications given the absence of leads and a device pocket. Successful implantation from the septal location has been described using the Micra Transcatheter Pacing System (TPS) (Medtronic Inc, Minneapolis, MN) introducer sheath, a Micra delivery catheter, or a steerable sheath that allows better alignment with the device and a loop snare. We report the case of a patient with a leadless pacemaker implantation because of atrial fibrillation with low ventricular response with an endocarditis on prosthetic mechanical mitral valve.